Thyroid cancer incidence trends by histology in 25 countries: a population-based study. Issue 4 (April 2021) - Miranda-Filho, Adalberto; Lortet-Tieulent, Joannie; Bray, Freddie; Cao, Bochen; Franceschi, Silvia; Vaccarella, Salvatore; Dal Maso, Luigino
Summary: Background: The incidence of thyroid cancer has increased in different populations worldwide in the past 30 years. We present here an overview of international trends of thyroid cancer incidence by major histological subtypes. Methods: We did a population-based study with data for thyroid cancer incidence collected by the International Agency for Research on Cancer (IARC) for the period 1998–2012. Data were extracted from the Cancer Incidence in Five Continents plus compendium. We selected data for 25 countries that had a population of more than 2 million individuals covered by cancer registration (87 registries in total). Further criteria were that the selected registration areas had to have a proportion of unspecified thyroid cancer of less than 10% and analyses were restricted to individuals aged 20–84 years. We calculated age-specific incidence rates and age-standardised rates per 100 000 person-years for individuals aged 20 to 84 years, and assessed trends by country, sex, and major histological subtype (papillary, follicular, medullary, or anaplastic) based on absolute changes in age-standardised incidence rates between 1998–2002 and 2008–12. Findings: Papillary thyroid cancer was the main contributor to overall thyroid cancer in all the studied countries, and was the only histological subtype that increased systematically in all countries, although with large variability between countries. In women, the age-standardised incidence rate of papillary thyroid cancer during 2008–12 ranged from 4·3–5·3 cases per 100 000 person-years in the Netherlands, the UK, and Denmark, to 143·3 cases per 100 000 women in South Korea. For men during the same period, the age-standardised incidence rates of papillary thyroid cancer per 100 000 person-years ranged from 1·2 cases per 100 000 in Thailand to 30·7 cases per 100 000 in South Korea. In many countries in Asia, the increase in papillary thyroid cancer rates in women was particularly pronounced after the year 2000; rates stabilised since around 2009 in the USA, Austria, Croatia, Germany, Slovenia, Spain, Lithuania, and Bulgaria. Temporal trends for follicular and medullary thyroid cancer did not show consistent patterns across countries, but slight decreases were seen for anaplastic thyroid cancer in 21 of 25 countries between 1998–2002, and 2008–12. In 2008–12, age-standardised rates for the follicular subtype ranged between 0·5 and 2·5 cases per 100 000 women (and between 0·3 and 1·5 per 100 000 men), while those for the medullary subtype were always less than 1 case per 100 000 women or men, and for anaplastic thyroid cancer less than 0·2 cases per 100 000 women or men. Interpretation: In the period from 1998 to 2012, the rapid increases in thyroid cancer incidence were observed only for papillary thyroid cancer, the subtype more likely to be found in a subclinical form and therefore detected by intense scrutiny of the thyroid gland. Funding: French Institut National du Cancer, Italian Association for Cancer Research, Italian Ministry of Health.